Esoteric Story of the Relationship between Transformational Leadership Style of the Field Managers and Salespersons’ Performance: Evidence from the Pharmaceutical Sector - Faheem Ahmad Khan; Muhammad Umer Quddoos; Ammara Akram; Arslan Ahmad Siddiqi (Journal of Accounting and Finance in Emerging Economies, 2025)
Purpose: In this unbendable competitive environment, pharmaceutical firms need to use the most appropriate field managers’ leadership style that is best suited for their sales force effectiveness, this study aims to highlight the prominence of the transformational leadership style of field managers and the significance of the salespersons’/medical representatives’ performance in an outbound pharmaceutical selling context and how work meaningfulness and work engagement can affect the performance of salespeople by using the mediating mechanism.